Analysing Financial Performance of Indian Automobile Sector in context of achieving Sustainability (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2023)
Manufacturing sector has occupied  an important role in India’s Economic  Development. India is globalising its product  more worldwide by ensuring vocal about  local products which in turns leading to more  start-ups, self-production, and employment  opportunities’. Self-reliant is leading India  towards sustainability. Sustainability focuses  on meeting the needs of the present without  compromising the ability of future generations  to meet their needs. In India, focus on  Manufacturing sector have been increased  to make India self-reliant and generate more  employment opportunities. Prime Minister of  India, Mr. Narendra Modi, had launched the  ‘Make in India’ program to place India on the  world map as a manufacturing hub and give  global recognition to the Indian economy.  The Government of India has taken several  initiatives to promote a healthy environment  for the growth of Manufacturing Sector in the  country. The Manufacturing Sector of India  has the potential to reach US$ 1 trillion by  2025 with impetus on developing industrial  corridors and smart cities; the government  aims to ensure holistic development of the  nation. The corridors would further assist  in integrating, monitoring, and developing  a conducive environment for the industrial  development and will promote advance  practices in Manufacturing Sector. India is  an attractive hub for foreign investments in  the Manufacturing Sector. Several mobile  phone, luxury and automobile brands, among  others, have set up or are looking to establish  their manufacturing bases in the country. In  today’s COVID19 pandemic, there is focus  of India to be self -reliant and every country  is promoting its Manufacturing Sector. In  this paper, financial performance and Capital  structure of Automobiles sector listed on BSE  500 for last 10 years will be analysed to know  the overall growth of this sector for making  India self- reliant. Various parameters will be  analysed in relation to ratios, trend analysis,  descriptive statistics, correlation for predicting  the growth of automobile sector in the last ten years. Data will be collected from CMIE  Prowess. Government initiatives to boost up the  manufacturing sector will also be analysed. This  paper will help Government, Policy Makers,  Industrialist, and the Economist to find more  paved ways of economic development through  automobile manufacturing sector.
Keywords: Sustainability; Start-Ups; Financial Performance; Capital Structure; Manufacturing Sector; Make in India; Automobile Sector